KEDUDUKAN OMNIBUS LAW DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Diani, Rosida (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2020)
An omnibus law into a new diskursus among all these observer , academics , politician , some groups obtained to having an interest to the product of law ( especially in the act of copyright with their new working been ratified by parliament. As a concept that is basically having no roots historical , theoretical , as well as practical in the indonesian legal system , the application of law is considered an omnibus would bring them to various kinds of serious debate if it is associated with the act of regarding the formation of legislation. For, known as, the bill does not set a clause on the concept of an omnibus, law in practice accommodate berbagaimacam kinds of topics and problems into one product, legislation for the legislation we are just following the principle of single, one the act of one particular subject / certain problems. Writer willing to this by asking problems up the theme and 1 ).Why government to use the law to an omnibus who are not known in the indonesian legal system. and 2) How a omnibus law in the indonesian legal system; normative juridical by using the method. Writers strove colaboration these problems and place into normative logic that is in the formation and regulations in indonesia. Writer came to the conclusion that the government should in perform the process transplant new law into the system our laws , should be seen a legal framework of us who have been raw , and how benefit the concept of these foreign to the needs of the people